Advances in Visual Informatics 4th International Visual Informatics Conference, IVIC 2015, Bangi, Malaysia, November 17-19, 2015, Proceedings - Badioze Zaman, Halimah; Robinson, Peter; Smeaton, Alan F.; Shih, Timothy K.; Velastin, Sergio; Jaafar, Azizah; Mohamad Ali, Nazlena; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the Fourth International Conference on Advances in Visual Informatics, IVIC 2015, held in Bangi, Malaysia, in November 2015. The five keynotes and 45 papers presented were carefully reviewed and selected from 82 initial submissions. The papers are organized in four tracks on visualization and big data; machine learning and computer vision; computer graphics; as well as virtual reality.
Visualization and big data -- Machine learning and computer vision -- Computer graphics -- Virtual reality.
Keywords: Computer science; Algorithms; User interfaces (Computer systems).